Evaluating the immunogenicity of an intranasal vaccine against nicotine in mice using the Adjuvant Finlay Proteoliposome (AFPL1). Issue 8 (August 2016) - Fraleigh, Nya L.; Boudreau, Justin; Bhardwaj, Nitin; Eng, Nelson F.; Murad, Yanal; Lafrenie, Robert; Acevedo, Reinaldo; Oliva, Reynaldo; Diaz-Mitoma, Francisco; Le, Hoang-Thanh
Abstract: Tobacco smoking is recognized as a global pandemic resulting in 6 million deaths per year. Despite a variety of anti-smoking products available to aid with tobacco cessation, the majority of people who attempt to quit smoking relapse within 6 months due to the addictive nature of nicotine. An immunotherapy approach could offer a promising treatment option by inducing a potent selective antibody response against nicotine in order to block its distribution to the brain and its addictive effects in the central nervous system. Our nicotine vaccine candidate was administered intranasally using the Neisseria meningitidis serogroup B Adjuvant Finlay Proteoliposome 1 (AFPL1) as a part of the delivery system. This system was designed to generate a robust immune response by stimulating IL-1β production through Toll-like receptor 4 (TLR4), a potent mechanism for mucosal immunity. The vaccine induced high antibody titers in mice sera in addition to inducing mucosal antibodies. The efficacy of our vaccine was demonstrated using in vivo challenge experiments with radioactive [ 3 H]-nicotine, followed by an analysis of nicotine distribution in the lung, liver, blood and brain. Our results were encouraging as the nicotine concentration in the brain tissue of mice vaccinated with our candidate vaccine was four times lower than in non-vaccinated controls; suggesting that the anti-nicotine antibodies were able to block nicotine from crossing the blood brain barrier. In summary, we have developed a novel nicotine vaccine for the treatment of tobacco addiction by intranasal administration and also demonstrated that the AFPL1 can be used as a potential adjuvant for this vaccine design.